PERAN PEMERINTAH DAERAH DALAM PEMENUHAN HAK PENYANDANG DISABILITAS PADA SARANA DAN PRASARANA HALTE TRANSJAKARTA DI JAKARTA BARAT: Local Government’s Role in Fulfilling the Rights to Facilities for Disable People at West Jakarta’s Transjakarta Bus Stops - Jihan Nabilah; Reni Dwi Purnomowati (Faculty of Law, Universitas Trisakti, 2025)
Local governments have the authority to fulfill the rights of Persons with Disabilities as stipulated in Law Number 8 of 2016 concerning Persons with Disabilities. The problems discussed in this study are related to the form of the role of local governments in fulfilling the rights of Persons with Disabilities in the facilities and infrastructure of the Transjakarta bus stop in West Jakarta and whether the services provided are in accordance with the laws and regulations. The type of research used normative legal research type using secondary data as the main data and primary data in the form of interviews as supporting data. Based on the results of the analysis in this study, it was found that there are still problems related to the facilities and infrastructure of the Transjakarta bus stop and there are no special regulations regarding maintenance provisions for the existing facilities and infrastructure of the Transjakarta bus stop. So there needs to be better coordination with related agencies such as the Transportation Department to carry out supervision and evaluation and the Highway Service to carry out development related to infrastructure such as pedestrian crossing bridges.